Modern interpretation of anatomical differences of liver, gallbladder and bile ducts of the children of different age groups - Maksudbekovna, Bakhtiyarova Aziza; Qabulovna, Masharipova Khulkar (PT. Antis International Publisher, 2024)
This article discusses gall bladder and liver diseases that are common in young children and adults. In addition, the anatomical differences of the liver, gall bladder and bile ducts were discussed.